Daya Saing Komoditas Tanaman Buah-Buahan di Kabupaten Ogan Ilir Sumatera Selatan - Septinar, Helfa; Utomo, Budi; Kesumaputri, Mega (Seminar Nasional Lahan Suboptimal, 2023)
Septinar, H., Utomo, B., Kesumaputri, M. (2023). Competitiveness of fruit crops in Ogan Ilir, South Sumatra County. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 734-741).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Horticultural crops have a big market. This can boost the community's economy. Fruit is a type of horticultural plant. It offers health benefits for our bodies. It also drives the economy in Ogan Ilir Regency. Consequently, this study focuses on the competitiveness of fruit plants in each sub-district of Ogan Ilir district. This study is a qualitative analysis that uses second-hand data from the Central Statistics Agency (BPS) and examines the RCA comparative advantage index (Revealed Comparative Advantage). It shows that fruit plants in the Ogan Ilir district are competitive for export. In 16 areas, 18 kinds of fruit are grown: avocado, starfruit, duku, durian, water guava, jamnu biji, big orange, siamese orange, manga, jackfruit, pineapple, papaya, banana, rambutan, sapodilla, soursop, and breadfruit. However, only seven types of fruit are competitive. Two of the 16 areas are competitive: Tanjung Batu and Payaraman. The competitiveness index for each sub-district is as follows: Tanjung Batu has a value of 2.21 and Payaraman has a value of 1.84. The fruits grown in this area include avocado, durian, Siamese orange, manga, pineapple, papaya, and banana. The tropical climate in Ogan Ilir allows these fruits to grow exceptionally well.